P-139 Adherence to Biologic Therapies in Inflammatory Bowel Disease. (February 2017) - Wentworth, Brian; Overby, M; Behm, Brian
Abstract : Background: Biologic therapies have proven efficacy in inflammatory bowel disease (IBD). The clinical effectiveness of therapy is dependent in part on medication adherence, and patient non-adherence to biologic therapy is associated with increased risks of disease exacerbation and immunogenicity. The aim of this study was to assess adherence rates and risk factors for non-adherence for different biologic therapies in an IBD population. Methods: A retrospective chart review was performed on a cohort of adult IBD patients at our institution prescribed biologic medications from September 2014 to September 2015. Inclusion criteria were: adult age (≥18 yr) and treatment with a biologic medication for ≥3 months. Patients were excluded if they were transitioning care or had a dose interruption secondary to acute illness, surgery, or loss of insurance. Patient demographics and risk factors for non-adherence were assessed. For self-administered therapies, specialty pharmacies were contacted to determine the number of medication shipments each patient received. Adherence was assessed using a modified Medication Possession Ratio (# home medication deliveries or infusions completed divided by the expected # of such events). Statistical analysis was performed using 2-tailed student's T tests and Chi Square tests. Results: One hundred seventy-five patients (mean age 40.1 yr, 61% female, 80% Crohn's) were included in the analysis. Of these patients, 37 (21%) failed to receive at least one scheduled infusion or medication shipment, and 20 (11%) failed to receive greater than 20% of their infusions or medication shipments. Biologic adherence rates were as follows: infliximab 84%, adalimumab 71%, certolizumab pegol 77%, and vedolizumab 87%. Patients receiving facility-administered therapies had significantly higher rates of adherence compared with those patients receiving self-injections (86% facility-administered versus 71% home administered, P = 0.021). Non-adherence was associated with lack of commercial insurance (30% versus 20%, P < 0.001) and was inversely associated with proximity to the medical center (mean mileage 93.6 versus 69.3, P = 0.048). Non-adherent patients were found to have higher rates of psychiatric disease (52% versus 37%), but this was not statistically significant. Non-adherence was not associated with patient age, gender, marital status, or disease activity in this patient population. Conclusions: The rate of biologic non-adherence was 21% in our IBD patient population, which is consistent with rates found in previous studies. Patient adherence was increased with facility-administered therapies (i.e., infliximab, vedolizumab) and commercial insurance, and an inverse relationship between proximity to the medical center and adherence was noted. Vedolizumab adherence was similar to infliximab in this patient population.